The status of Algeria’s sea cucumbers and their illegal trade - MEZALI, Karim; Slimane-Tamacha, Farah (SPC Beche-de-mer Information Bulletin #40, 2020)
In Algeria, sea cucumber fishing is mainly done by divers and gleaners who target all holothurian species along the coast, especially the ones found in shallow water. To better understand how this fishery is organised, a survey took place from August to September 2018. Face-to-face interviews with fishers (gleaners and divers), members of coastal communities and local traders were carried out to gather detailed information on the fishery. In addition, an online survey was developed to allow stakeholders to respond anonymously. Seventy-eight responses were received from fishers and middlemen who were very familiar with the fishing and trade. These responses were received from 14 different wilayas (administrative areas) spread along the Algerian coast. The wilaya of Tipaza was found to be the most active in the fishery, followed by Mostaganem, Jijel and Algiers. Sea cucumber processing methods, sales and prices are also discussed, as well as, given the rapid development of the sea cucumber fishery, the urgent need for its effective management.
Keywords: Sea cucumber, survey, illegal fishing, Algerian coastal waters